Rapidly Establishing a Hospital-Based Convalescent Plasma Collection Center With the Alyx Apheresis Collection Device - Tovah Klein BA; Rita Elue DNP; Sachie Ikegami MD, PhD; Christopher Mikkelson BS; Gregory Wright BS; Jessica Mallek AA; Jason Kang MD; David J. Sullivan MD; Thomas J. Gniadek MD, PhD (Elsevier, 2021)
The effort to collect convalescent plasma from individuals who recovered from COVID-19 began in earnest during the spring of 2020. Either whole blood or apheresis donations were obtained, the latter yielding higher numbers of units per donor per collection and more frequent collections. The NorthShore University HealthSystem blood donor center purchased 2 Alyx (Fresenius Kabi) apheresis plasma collection devices and quickly implemented them in order to collect COVID-19 convalescent plasma. Apheresis-experienced and inexperienced phlebotomists operated the instruments. Donors were collected >14 days from symptom resolution and all donors were negative by SARS-CoV-2 nasopharyngeal swab. Both internal metrics of performance as well as a post donation survey were used to evaluate the feasibility implementing this collection program. During the first 100 days of the collection program, 650 plasma units were collected. In particular, during the first week of the program, 38 units were collected and distributed to hospitals under the emergency investigational new drug and expanded access program. Fifty-one donors (15%) were deferred due to vital signs out of range or donor screening questions. Thirty-one donors (10%) were deferred due to positive nasopharyngeal swab. Lower than target yield occurred in 16.6% of collections due to donor reactions or flow errors. Donors rated the overall program lower, but not the staff, when they reported symptoms related to collection. In conclusion, a hospital-based apheresis convalescent plasma collection program can be rapidly implemented. Donor reaction rates and vein infiltration rates should be carefully monitored for each phlebotomist.